Analisis Implementasi Peraturan Pajak Penghasilan 23 dan Kepatuhan Terhadap Peraturan Perpajakan Terkait Pelayanan Maklon Pada Perusahaan PT. X tahun 2019 - Adang, Ferry; Yuliana, Khrisna Anggun; Sulivyo, Lod (LPPM STIE PPI, 2023)
Introduction/Main Objectives: This research the application of Pph rule 23 for services of minors is determined based on Minister of Finance Regulation Number 141/PMK.03/2015, in the calculation of which a tax of 2% is applied. Background Problems: esearchers examine the realization and objectives of tax revenues to find out whether PPh 23 deductions have increased or decreased. Examining routine PPh Article 23 SPT reporting is one way to ensure compliance with PPh deductions Novelty: The aim of this research is to determine the suitability of the application of income tax article 23 and taxpayer compliance in relation to maklon at PT. X. Research Methods: The type of research used is qualitative research using descriptive methods. Finding/Results: The results of this research indicate that the implementation of Article 23 Income Tax deductions carried out by PT. X is in accordance with Minister of Finance Regulation Number 141/PMK.03/2015. Conclusion: In terms of compliance with taxpayer compliance with payments and reporting, PT. X In the payment and reporting of Article 23 Income Tax there is no delay and has been fully in accordance with the Taxation Provisions of Law No. 36 of 2008.